Management of a R&D portfolio: a 0-1 integer linear programming model - Costa, A.; Paixão, J.P (Congresso da APDIO - IO 2013, 2013)
We introduce a 0-1 integer linear programming model for a R&D portfolio with a budget constraint. Considering that the budget is associated to the development phase, in the formulation presented, we determine the optimal decision policy for each project, as a series of improvement / continuation / abandonment options, in each stage of the development phase that respects the limited budget and maximizes the overall value of the portfolio. Accordingly to the computational experience developed, we draw the main conclusions relatively to the adoption of this mathematical model. Further, we discuss the possibility of incorporate additional managerial choices in the formulation presented.